New Technologies for Promoting Physical Activity in Healthy Children and in Children with Chronic Respiratory Diseases: A Narrative Review - Velia Malizia (MDPI AG, 2021)
Physical activity (PA) is proven to benefit children and adolescents in several ways. New technologies may provide children with stimulating modalities for organizing their leisure time, accessing fitness programs, and obtaining daily goal reminders and peer support. Due to the current COVID-19 pandemic, following WHO recommendations for PA is difficult for many children, especially for those living in urban areas. Therefore, the use of digital tools to support and maintain PA could be useful in healthy children, as well as in those with chronic respiratory diseases (CRDs). This narrative review aims to summarize the most recent evidence about the role of new technologies in promoting PA in healthy children and in those with CRDs, in supporting PA during the COVID-19 pandemic, and in enhancing psychological wellbeing in this age group. The use of technological devices for promoting PA, such as web/mobile apps and games, has been proven to be effective both in healthy children and in those with CRDs. In conclusion, new technologies are very promising in terms of feasibility, acceptability, and efficacy in promoting PA. Further studies are required to evaluate the long-term health benefits of using these technologies.